The Effect of ICT use in Teaching and Learning on Students' Achievements - Sadanandan, C. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Information and communication technologies (ICT) have become commonplace entities in all aspects of life. Technology is moving rapidly in recent times than our ability so we need to adapt and adopt the new way of technology to improve to gather information in our daily affairs to save our money, energy and large amount of time. Across the past twenty years the use of Information and Communication Technology (ICT) has fundamentally changed the practices and procedures of nearly all forms of endeavor within business and governance. Education is a very socially oriented activity and quality education has traditionally been associated with strong teachers having high degrees of personal contact with learners Nowadays, ICT plays a vital role to reduce mass illiteracy and help to overcome the educational problems faced during the development of Digital India. IT is a discipline deals with Science, Technology, Engineering and Management in handling information, its applications associated with social, economic and cultural matters. Currently, 90% of the world‟s population depends on internet technology and related gadgets to fulfil their basic needs of their routine life. This technological revolution is very important for all over human development in this smart world, especially in educational field. It makes the process of teaching-learning and evaluation more fascinating, easy to understanding and all involving with a smoother application. Even the government also promotes ICT based learning tools from primary level to degree level courses for practically sound knowledge and expanding expertise in their specific field. Students from any corner of the world can share their knowledge and solve their difficult experiments, problems with other researcher. In many fields of study, ICT based learning is useful to improve understanding of practical knowledge. There are so many applications based on ICTs. This paper focuses on methodologies of ICT in recent challenges of ICT in outcome based teaching and learning Pedagogy. Different Strategies for teachers to apply ICTs, various tools for different purpose like accessibility   of   distance learning, evaluation, scholastic Performance, e-courses and virtual classroom for qualitative and productive educational culture. In Kerala even though the government introduced IT@school project in general education schools from 2001 onwards, in teaching learning process ICT enabled education is not yet facilitated completely. In 2017 onwards it is started “Samagra” eResource portal to enrich the Hi-tech classrooms with ICT equipment and trained teachers. This study is aimed to identify the relationship between the Information and Communication Technology use in teaching and learning towards the achievement of secondary school students in Science subject. A total of 80 respondents were selected amongst 8th standard students in Pantheerankave HSS, Kozhikode, and Kerala. Quantitative approach has been used in this study. Students were classified into two groups namely the teaching using ICT and teaching without using ICT. The t-test showed higher value for the ICT group as compared non ICT Group.  The findings showed positive relationship between ICT use in Science lessons and the students‟ achievements/ learning outcome. The usage of ICT during lessons conducted in classes has improved the learning outcomes of students and therefore the contribution should be recognised by all teachers in order to enhance students‟ achievement in academic. Based on the findings, several recommendations have been made to provide some insights into the application of ICT in Science subject. The result indicated that ICT use in teaching and learning process increased the students‟ achievement in Science subject in the school.